(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
Field experiments were conducted on pastoral and agro-pastoral areas of South Omo Zone at Dasenech, Hammer and Gynagatom woredas of South Omo Zone, Southern Ethiopia on four cowpea [Vigna unguiculata (L) Walp.] varieties in 2019 under irrigation. The objective of the study was to select the best performing cowpea varieties in the target areas. The cowpea varieties included in the field experiment were (Black eye bean, Bole, TVU, and Kankeit). The experiments were carried out using a randomized complete block design (RCBD) with three replications. The combined analysis of variance results depicted that there were significant differences among the varieties for all the studied parameters except the number of seeds per pod. The mean values for plant height ranged from 84.89 (cm) for the variety Bole to 120.67 (cm) for TVU. The mean values for the number of pods per plant ranged from 24.33 for the variety Bole to 46.90 for TVU. The mean value for 100 seeds weight was maximum (21.11g) for the cowpea variety black eye bean and, while it was minimum (17.11 g) for the variety TVU. The highest overall mean grain yield of 2457.0 kg ha-1 was recorded for the variety Kankeit while the minimum 1695.3 kg ha-1 was noted for the cowpea variety black eye bean. Therefore, the variety Kankeit and TVU could be recommended for the study areas however further research should be done to put the recommendation on a strong basis. Int. J. Agril. Res. Innov. Tech. 12(1): 137-140, June 2022